Efeito do extrato de Cynara cardunculus L. na degradação, hidrólise e perfil de caseínas do Queijo Serpa - Garrido, Ana (2020)
CYNARA CARDUNCULUS. L AQUEOUS EXTRACT EFFECT ON DEGRADATION, HYDROLYSIS AND CASEIN PROFILE OF SERPA CHEESE ABSTRACT: The effect of Cynara cardunculus L. aqueous extracts (C1, C2, C3) was studied on Serpa PDO cheese proteolysis, during maturation (D1, D14, D35). Proteolysis was assessed by polyacrylamide gel electrophoresis with urea and by Kjeldahl methods. A casein profile pattern was found, and results showed a higher αs-CN degradation than β-CN. Results (R2≥80%) showed, that a linear regression model can be used to predict the degradation product of αs-CN, the pre-αs-CN during more ripening phases. Casein hydrolysis was found to be more extensive in cheeses made using Cynara cardunculus L., which was confirmed by the higher levels of IEP during maturation on these cheeses. On the other hand, the degree of proteolysis in terms of IPP was similar in cheese produced using vegetable or animal coagulant. The evaluation of Queijo Serpa proteolysis and the deduction, through a LRM, of the αs-CN degradation products can be a way to add some value to the use of Cynara cardunculus L. in cheesemaking and to a socioeconomic valorization. Keywords: Cynara cardunculus L; Queijo Serpa; caseins; proteolytic index.